Comparative Acute Toxicity of Glyphosate-Based Herbicide (Gbh) to Daphnia Magna, Tisbe Longicornis, and Emerita Analoga - Villamar-Ayala, C (Taylor and Francis Inc., 2020)
The aim of this work was to know the differential composition of the dissolved fraction of a glyphosate-based herbicide (GBH), commercialized as GLIFOPAC, when reaches different aquatic environments and its ecotoxicological effects on crustaceans species living in them. Daphnia magna, Tisbe longicornis, and Emerita analoga were exposed to glyphosate herbicide called GLIFOPAC (480 g L−1 of active ingredient or a.i.) at concentrations between 0.5 and 4.8 g a.i. L−1. Acute toxicity in D. magna (48 h-LC50), E. analoga (48 h-LC50), and T. longicornis (96 h-LC50) was studied. Chromatographic analysis of the GBH composition used and water (freshwater/sea water) polluted with GLIFOPAC were evaluated. Results reported acute toxicity (48–96 h-LC50) values for D. magna, E. analoga and T. longicornis of 27.4 mg L−1, 806.4 mg L−1, and 19.4 mg L−1, respectively. Chromatographic evaluation described around 45 substances of the GLIFOPAC composition, such as from the surfactant structures (aliphatic chain with esther/ether group), metabolites (AMPA), and other substances (glucofuranose, glucopyranoside, galactopyranose). This study evidenced differences in the GLIFOPAC composition in freshwater and marine water, which may differentiate the toxic response at the crustacean-level in each aquatic environment. © 2020, © 2020 Taylor & Francis Group, LLC.